Optimization of the Implementation of the Livable Housing Assistance Policy by the Kepulauan Sula Regency - Soamole, Sri Reziki; Khairunnisa, Atikah; Rolobessy, Mike Jurnida (Baileo: Jurnal Sosial Humaniora, 2024)
This study aims to analyze the optimization of the implementation of the Decent Habitable House (Rumah Layak Huni or RLH) Assistance policy in Sulabesi Tengah District, Kepulauan Sula Regency, North Maluku. The research investigates how the policy, designed to improve housing conditions for low-income communities, aligns with the standards established in Law No. 1 of 2011 on Housing and Settlement Areas. Employing a structured descriptive qualitative approach, data were collected through interviews, observations, and document analysis to assess policy execution, institutional coordination, and social impacts. The findings reveal that the RLH program has contributed positively to the welfare of low-income residents by improving access to livable housing. However, the program also faces several persistent challenges, such as rising construction costs due to increases in fuel prices and limited coordination and communication among central, regional, and village governments. The roles of the Head of the Department and the Head of the Housing and Settlement Area Division are pivotal in overseeing, supervising, and evaluating program implementation. Additionally, social tensions and issues in verifying eligible recipients highlight the need for clearer criteria and more inclusive communication. Periodic evaluations are crucial for addressing these concerns and enhancing program effectiveness. The novelty of this study lies in its detailed examination of housing policy implementation in a remote island regency context, contributing fresh insights into public policy execution in peripheral regions. The study recommends strengthening intergovernmental coordination, improving beneficiary targeting, and institutionalizing regular monitoring and evaluation to support the advancement of social and human sciences in the area of inclusive development policy.